Relationship Between the Cognitive Process and the Clarity of Circumstances of Committing a Criminal Offense During the Pre-Trial Investigation - Skripkutė, Greta (Teisė, 2024)
The article analyses the relationship between the cognitive activity and the clarity of circumstances of committing a criminal offense. To establish this connection, the cognitive process is divided into two parts: the recognition conducted by officials during the observation of the criminal act, and the completed criminal offense recognition, discussing nuances of the witness recognition process in this section. After conducting the analysis, it was determined that the level of clarity varies depending on the stage at which the subjects with the burden of proof – officials – become familiar with the criminal offence, i.e. only the knowledge performed by the officers is enshrined in the procedural expression of their cognitive activity – protocols, which help to decide on the fulfilment of the condition of clarity (not), and when getting acquainted with the completed act, the cognitive activity of the witnesses, which is revealed during communication with the officers (interrogation), is also of great importance. The article discusses issues related to protocol drafting, encompassing objective and subjective elements, the impact of witness interviews on the clarity of circumstances surrounding the commission of a criminal offense, the role of the pre-trial judge, and the evaluation of the clarity conditions in simplified procedures in judicial practice.